2020
DOI: 10.3390/ph13120441
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3σ and Its Modulators in Cancer

Abstract: 14-3-3σ is an acidic homodimer protein with more than one hundred different protein partners associated with oncogenic signaling and cell cycle regulation. This review aims to highlight the crucial role of 14-3-3σ in controlling tumor growth and apoptosis and provide a detailed discussion on the structure–activity relationship and binding interactions of the most recent 14-3-3σ protein-protein interaction (PPI) modulators reported to date, which has not been reviewed previously. This includes the new fusicocca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 111 publications
1
16
0
Order By: Relevance
“…Previous studies have identified 14-3-3σ as a tumor suppressor as it plays a pivotal role in controlling tumor metabolic reprogramming and thus cancer cell growth and metastasis [ 23 ]. For example, it has been reported that 14-3-3σ protects P53 against MDM2-mediated ubiquitination and degradation, resulting in direct control of the G2-M checkpoint of the cell cycle [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified 14-3-3σ as a tumor suppressor as it plays a pivotal role in controlling tumor metabolic reprogramming and thus cancer cell growth and metastasis [ 23 ]. For example, it has been reported that 14-3-3σ protects P53 against MDM2-mediated ubiquitination and degradation, resulting in direct control of the G2-M checkpoint of the cell cycle [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, to date, no ligand has been reported to target the central cavity of the dimer interface of the 14-3-3σ and stabilize its homodimeric form, as the reported modulators of 14-3-3σ (both stabilizers and inhibitors) generally target the amphipathic ligand-binding groove [ 23 , 51 ]. Nevertheless, one ligand (GCP-Lys-OMe) has been recently reported to bind to the dimer interface of the 14-3-3ζ isoform [ 47 ], though it is not known if the compound can stabilize the 14-3-3ζ dimer.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the design and our results, it is presumed that TDPP could have great degradation efficiency for proteins with those three kinds of motifs. While 14-3-3 and P-14-3-3-BME proteins are involved in many cellular events, including neural development (Antunes et al, 2022), cancer proliferation and apoptosis (Aljabal and Yap, 2020; Huang et al, 2020; Yang et al, 2020), autoimmune disorder (McGowan et al, 2020), virus infection (Liu et al, 2021), etc., the TDPP-induced degradation could be significant in regulating the related downstream pathways and biological events.…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight a role for 14-3-3η binding to FOXO3 in invadosome formation and suggest that this event may become an attractive target for countering the ECM-degradative capacity of RA synoviocytes. In keeping with this possibility, various compounds targeting 14-3-3 protein interactions are in development, with potential therapeutic implications in other disorders such as cancer and neurological disorders [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%